ANALISIS PENGARUH BEBAN KERJA TERHADAP TINGKAT STRES KERJA PEMBIMBING KEMASYARAKATAN DI BAPAS KELAS I BANJARMASIN - Noor Cahaya; Ceria Hermina (Fakultas Psikologi Universitas Wijaya Putra, 2023)
Work stress is an interaction between working conditions and worker characteristics that change normal physical and psychological functions. Job stress arises as a form of individual incompatibility with the work environment. One of the factors that affect work stress is workload. This study aims to look at the effect of workload on the work stress of the social counselor of the Banjarmasin Class I Bapas. The research method used is a quantitative method with a correlational design. Data collection tools used are the Workload scale and Work Stress scale. Subject taking technique using total sampling. There are 38 subjects in total. The data analysis used is simple linear regression analysis. The results of the researchers showed that the workload affected the work stress of the community counselors of the First Class of the Banjarmasin Fathers. Workload affects work stress by 10.9% (R2=0.109; F(4.409) = sig <.043). Based on these results, the research hypothesis is accepted, namely that there is an effect of workload on the work stress of community supervisors of the First Class Bapas Banjarmasin.